Business letters for all - Naterop, B. Jean (Bertha Jean); Weis, Erich; Haberfellner, Eva (Kuala Lumpur ; Oxford : Oxford University Press, 1977)
English level: Intermediate to Advanced Description A guide to British and American business correspondence. Who is it for? Anyone who deals with correspondence in a business setting. Key features Letter-writing exercises and example letters with comprehension questions. Guidance and practice for letters covering topics such as payments, sales, orders etc. Help also given with the social letters that are important for business contacts, such as formal and informal invitations, congratulations, or thanks for hospitality.
Published in Malaya: 1977.
1
Keywords: Commercial correspondence; Business correspondence